2014
DOI: 10.1155/2014/708593
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Etoposide in CT-26 Cells of Colorectal Cancer Using Folate Targeted Dextran Stearate Polymeric Micelles

Abstract: Targeted drug delivery using folate receptors is one of the most interesting chemotherapeutic research areas over the past few years. A novel folate targeted copolymer was synthesized using dextran stearate coupled to folic acid. FT-IR and NMR spectroscopy were used to confirm successful conjugation. Micelles prepared using this copolymer were characterized for their particle size, zeta potential, critical micelle concentration (CMC), drug loading capacity, and release efficiency. Cytotoxicity and cellular upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The NPs having the size around 100 to 200 nm gathered much efficiently in solid tumors than normal tissues. They also said that folate-targeted NPs might enter inside the tumor cells by endocytosis which is mediated through folate receptor [87]. They have seen that the addition of free folic acid to the folate-free culture medium of CT26 cells, cell viability was enhanced to 51.98 ± 6.3%.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The NPs having the size around 100 to 200 nm gathered much efficiently in solid tumors than normal tissues. They also said that folate-targeted NPs might enter inside the tumor cells by endocytosis which is mediated through folate receptor [87]. They have seen that the addition of free folic acid to the folate-free culture medium of CT26 cells, cell viability was enhanced to 51.98 ± 6.3%.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…It could be explained that effective property of NLCs formula could facilitate greater cellular uptake than free drugs. The mechanism of action of ETP NLCs was proposed to be a cell uptake followed by a sustained drug release from the NLCs in combination with an intracellular P-gp inhibition ensuring a higher anticancer drug concentration inside the cancer cells (Varshosaz et al, 2014). Moreover, with the adding of the FA ligands, better cancer cell delivery effect of NLCs was observed than their non-modified ETP-NLCs counterparts.…”
Section: Cell Viability Studymentioning
confidence: 99%
“…It has been found that the half maximal inhibitory concentration (IC 50 ) of ETP using FA targeted dextran stearate polymeric micelles was 0.49 mg/ml for CT-26 cells while 9.41 mg/ml for the pure drug (Varshosaz et al, 2014). In a study on the antitumor activity, the uptake of FA-modified polymeric nanoparticles loaded with ETP by Hela cells and L929 cells was much higher than that of normal fibroblast cells (Kılıçay et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One of the alternative approach is to use metal radionuclide including 68 Ga (t 1/2 = 68 min, β + = 89% and electron capture (EC) = 11%), which can be obtained easily from 68 Ge/ 68 Ga generator without the serve of cyclotron. 8 [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%